Implications of Volatility in Quarterly Accounting Data: A Reply. - Kiger, Jack E. (The Accounting Review, 1975)
Abstract Presents a reply to the commentary on the study on volatility in quarterly accounting data. Difficulties which arise from the use of the dependent period concept to determine a number predictive of annual net income; Basis for dependent period concept; Causes of fourth quarter adjustments; Evidence for the existence of bath items.